Korekta kosztu kapitału w sytuacji braku równowagi parytetowej walut - Słoński, Tomasz (Estimation of Capital Cost under Disequilibrium on International Money Market, 2006)
In order to minimize firm's cost of capital debt denomination in foreign currency is frequently used. However, under these circumstances the calculation of capital cost might be difficult. This paper presents two methods of the cost of capital calculations under equilibrium and disequilibrium on the international money market
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 534-544